2021
DOI: 10.1002/chem.202103152
|View full text |Cite
|
Sign up to set email alerts
|

Iodine(I) and Silver(I) Complexes of Benzoimidazole and Pyridylcarbazole Derivatives

Abstract: The synthesis of iodine(I) complexes with either benzoimidazole or carbazole-derived sp 2 N-containing Lewis bases is described, as well as their corresponding silver(I) complexes. The addition of elemental iodine to the linear two-coordinate Ag(I) complexes produces iodine(I) complexes with a three-center four-electron (3c-4e) [NÀ IÀ N] + bond. The 1 H and 1 H-15 N HMBC NMR studies unambiguously confirm the formation of the complexes in all cases via the [NÀ AgÀ N] + ![NÀ IÀ N] + cation exchange, with the 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 76 publications
1
27
0
Order By: Relevance
“…It should be noted that despite the increasing asymmetry of the N 1 -I-N 2 bond, the N 1 -I-N 2 angle remains strictly linear (Table S2 †) even for [I(1)( 16)] + , enforced by the nature of the 3c-4e [N 1 ⋯I⋯N 2 ] + halogen bond in all halogen(I) complexes. [36][37][38][39][40]42,50,53 Mechanism of ligand exchange Similar to proposed mechanisms for halogen(I) transfer using three-centre iodine(I) complexes in organic synthesis, [54][55][56][57][58][59] the ligand exchange process in iodine(I) complexes can be addressed (Scheme 2). The reversible dissociation of the threecentre complex (e.g., [I( 7 It should be noted that the dynamic character of the bis(acyloxy)iodates(I)-related axles in rotaxanes was also studied by the group of Šindelář, in which the carbonyl hypoiodite was analogously suggested to be the key intermediate in the transfer of the iodine(I) ion among different axles.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that despite the increasing asymmetry of the N 1 -I-N 2 bond, the N 1 -I-N 2 angle remains strictly linear (Table S2 †) even for [I(1)( 16)] + , enforced by the nature of the 3c-4e [N 1 ⋯I⋯N 2 ] + halogen bond in all halogen(I) complexes. [36][37][38][39][40]42,50,53 Mechanism of ligand exchange Similar to proposed mechanisms for halogen(I) transfer using three-centre iodine(I) complexes in organic synthesis, [54][55][56][57][58][59] the ligand exchange process in iodine(I) complexes can be addressed (Scheme 2). The reversible dissociation of the threecentre complex (e.g., [I( 7 It should be noted that the dynamic character of the bis(acyloxy)iodates(I)-related axles in rotaxanes was also studied by the group of Šindelář, in which the carbonyl hypoiodite was analogously suggested to be the key intermediate in the transfer of the iodine(I) ion among different axles.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…31,[34][35][36] Considering the halogen(I) complexes possible from the myriad of potential ligands, the reported halogen(I) complexes in the CSD database are still limited. [37][38][39][40][41][42] The difficulty in obtaining single crystals of halogen(I) complexes sometimes makes it challenging to prove their formation, unless more definitive methods were available in solution. It has been reported that the 15 N NMR chemical shift change of the coordinated nitrogen can indicate the formation of an [N⋯I⋯N] + complex, 43 though not always conclusively, as the 15 N NMR chemical shift changes of the nitrogen atom in some protonated ligands also fall within similar expected ranges.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the more complex structure of the cages, the reaction requires more time for completion than for the previously reported small-ligand iodine( i ) complexes. 45 Upon completion of the reaction, the silver iodide (AgI) precipitates from the solution leaving the cationic tris-iodine( i ) cage with the three anions in the solution.…”
Section: Resultsmentioning
confidence: 99%
“…45 However, in the silver( i ) cage formation the N–Ag–N angles are more linear when compared to the simple mononuclear complexes where the anion to silver( i ) cation interactions can cause distortion from linearity. 45…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation